Effect of dietary patterns on mild cognitive impairment and dementia: a machine learning bibliometric and visualization analysis - Lou, Yan; Chen, Xueping; Zhao, Le; Xuc, Nan; Zhang, Lijun; Hu, Wenyi; Qiu, Yongzhen (Frontiers in Nutrition, 2024)
We declare that we have no financial and personal relationships with other people or organizations that can inappropriately influence our work, there is no professional or other personal interest of any nature or kind in any product, service and/or company that could be construed as influencing the position presented in, or the review of, the manuscript entitled, "Effect of dietary patterns on mild cognitive impairment and dementia: A machine learning bibliometric and visualization analysis" corresponding author: